Determination of the orientation coefficient for concrete elements reinforced with polyolefin fibers subjected to mixed mode fracture - Ramírez, Wladimir (2022)
During the last 60 years the use of concrete reinforced with fibers (HRF) has had a constant evolution. This technique allows the reduction of the traditional reinforcement by means of steel bars in the structural design of civil works and buildings. The fibers used from the beginning of the use of this technique have been those of steel, but in recent years other synthetic fibers have made their way into HRF. Thus, polyolefin macro fibers have been shown to meet the necessary requirements to be considered suitable in structural design. But this technological advance of polyolefin fibers must be supported by a deep knowledge of their characteristics and the way in which they are distributed within the structural elements. For this reason, in the present study the distribution of the fibers is analyzed through the orientation coefficient for concrete elements reinforced with polyolefin fibers (HRFP) subjected to mixed mode fracture tests, the results indicate that this tends to decrease relative to a vertical plane.